The Change of Cytokines and Gut Microbiome in Preterm Infants for Bronchopulmonary Dysplasia - Zhang, Zhenjie; Jiang, Jingjing; Li, Zhenghong; Wan, Weilin (Frontiers in Microbiology, 2022)
Background: Bronchopulmonary dysplasia (BPD) is a devastating form of chronic lung disease that develops in preterm infants. The BPD is speculated to arise from abnormal inflammatory responses which is related to the composition of commensal microbiota, leading us to hypothesize that the BPD susceptibility could be influenced by gut microbiota through inflammatory responses. This study is aimed to detect cytokines and the differences in fecal gut microbial composition in the BDP patients. Methods: Between June 2018 and June 2020, preterm infants born at gestational age ≤30 weeks were recruited. The clinical data of infant characteristics were collected. On day 3-7 and 14-28 after birth, fresh stool samples and serum were collected. The gut microbiota composition between the BPD group and controls was detected by 16S rRNA sequencing. On day 3-7 and day 14-28, ten cytokines include IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p70, IL-13, IFN-γand TNF-α were detected in the serum. Results: This study enrolled 38 preterm infants, the number of preterm infants in BPD group and control group was respectively 18 and 20. The gestational age [(27.4±1.5) vs. (29.5±0.9) weeks, P=0.000] and birth weight [(971±240)g vs. (1262±335)g，P=0.000] of the BPD group were lower than those of the control group. The present study found that the BPD group had high levels of IL-1β, IL-4, IL-6, IL-8, and TNF-α, whereas IL-10 was decreased. The Shannon diversity index of BPD group was lower. The relative abundances of Proteobacteria in BPD group increased significantly from Day 3-7 to Day 14-28, while the Firmicutes was decreased. On Day 14-28, the relative abundances of Proteobacteria in BPD group were significantly higher than Control group, while the Firmicutes was lower. Conclusion: The BPD could be influenced by gut microbiota through inflammatory responses. More studies were needed to explore the imbalance of cytokines and microbiome in BPD infants and whether it could be reversed by probiotics. This study provided a novel perspective for treating the BPD.